Թորոս Թորամանյանի գործունեությունը Բուլղարիայում - Զ. Մ. Ղասաբյան; Ն. Ծ. Պապուխյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Основатель армянской архитектурной науки Торос Тораманян свою профессиональную деятельность начал как архитектор-практик и строитель. Резня армян в Турции осенью 1895 г. заставила Т. Тораманяна переехать в Болгарию, где он оставался до 1900 г. Построенные им в Софии и Варне жилые дома и общественные здания отличались передовыми конструктивными решениями и самобытной архитектурой. The founder of Armenian architectural science Toros Toramanian began his professional activity as architect-practician and builder. The massacre of Armenians in Turkey in Autumn of 1895 made T. Toramanian move to Bulgaria, where he stayed till 1900. Houses and social buildings built by him in Sofia and Varna, varied with advanced constructive solutions and original archetecture.
Keywords: Biography; Auxiliary Sciences of History; N Fine Arts; NA Architecture